The power law model applied to the marathon world record - Fernández-Revelles, A. B.; Garcia Mármol, E. (Journal of Human Sport & Exercise, 2019)
In September 2013 the world record in the marathon men's race was broken. The aim of this study is to apply to the 2013 Berlin Marathon a mathematical model based on the power law that analyses the marks distribution and checks its connection. The results show that the correlations obtained in all the different categories have been very significant, with a result of (r = 0.978; p < 0.000) and a linear determination coefficient of (R2 = 0.969). As a conclusion it could be said that the power law application to the 2013 Berlin Marathon Men's race has been an useful and feasible study, and the connection between the data and the mathematical model has been so accurate.